„Aby pojąć Paryż, trzeba długo żyć z Paryżem”... Francuskie wrażenia z podróży Łucji z książąt Giedroyciów Rautenstrauchowej - Abramczyk, Magdalena (Colloquia Litteraria, 2013)
‘To grasp Paris, one has to live with Paris for a long time’. French impressions from journeys of Łucja Rautenstrauch from the ducal family of Giedroyć The article is a short attempt to present the reader with a profile of the now-forgotten Łucja Rautenstrauch from the ducal family of Giedroyć, a nineteenth century writer and traveller, who gained her fame and appreciation in the epoch thanks to her travel writings. Two of Łucja Rautenstrauch’s works deserve special attention: My memories of France [Wspomnienia moje o Francyi] and The last journey to France [Ostatnia podróż do Francyi], where she gave an impartial description of Paris. The author depicts the city pointing both to its good and bad sides. Her memories distinguish themselves from among other travel writings because of the author’s unusual sense of perception and the accuracy of her remarks. One will not find any instances of artificial admiration nor unnecessary humility in front of the people who meant more than her. On the contrary, an image of an educated aristocrat who does not feel the obligation to uphold the rules of the world she did not appreciate emerges for My memories of France. In the same work Łucja Rautenstrauch focuses on the description of the visible and external world: the customs, fashion, the French street, the salon and the history of the visited places.